Antioxidants of Maltease orange peel: comparative investigation of the efficiency of four extraction methods - Nouha M&#;hiri & , Ioannou Irina, Paris Cédric, Mohamed Ghoul, Nourhene Boudhrioua (Journal of Applied Pharmaceutical Science, 2017)
The effect of four extraction methods applied at 35°C (conventional solvent extraction, CSE, ultrasound assisted extraction, UAE, microwave assisted extraction, MAE and supercritical CO2 extraction, SC-CO2) on the total phenol contents, total flavonoid contents, individual flavonoids, vitamin C and antioxidant activity of orange peel was examined. Neohesperidin (from 0.624±0.013 for SC-CO2 extraction to 1.045±0.001g/100g orange peel powder for MAE) and hesperidin (from 0.407±0.008 for SC-CO2 extraction to 0.836±0.029g/100g orange peel powder for UAE) are the major flavonoids (80% of total flavonoids by MAE and 87% by CSE) of orange peel whatever the used extraction method. The method giving the highest total phenol and flavonoid contents is microwave assisted extraction (2.363±0.014 g GAE/100g orange peel powder), followed by ultrasound assisted extraction, conventional solvent extraction, and supercritical CO2 extraction. However, vitamin C content is not affected by the extraction method. Antioxidant activity (DPPH method) cannot be correlated to TPC, TFC or individual flavonoids. Orange peel extracted by CSE presents the highest radical scavenging capacity compared to the other extracts obtained by MAE, UAE and SC-CO2 extraction. Besides, no additivity on the antioxidant activity is found with the DPPH method.
Keywords: Orange peel, phenolic compounds, vitamin C, extraction methods, antioxidant activity.